The Influence of Product Quality, Brand Image, and Price Perception on The Purchase Decision of Honda Vario Motorcycles in Depok - Madani, Arfi Ulya; Karyatun, Subur; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study has several objectives, namely to analyze the influence of the independent variables of this study in the form of product quality, product image, and price perception on the dependent variables of this study in the form of purchasing decisions for Honda Vario motorcycles. The method used is descriptive-quantitative with a group of respondents or specifically with consumers of Honda Vario motorcycles. There are (four) variables including three independent variables in the form of product quality (X1), brand image (X2), price perception (X3), and variables bound to this study in the form of purchasing decisions (Y). The sample of respondents to the study amounted to 100 people with purposive sampling techniques. When purposive sampling techniques are used, it is expected that the sample meets the requirements or criteria needed in this study. The data used were primary, dividing the questionnaire with a model test in the form of linear regression processed with SPSS 25. The results of this study after analysis using data processing concluded that product quality, brand image, and price perception have a positive and significant influence on purchasing decisions.